Print reading for engineering and manufacturing technology - Madsen, David A. (Thomson/Delmar Learning, 2004)
This enhanced edition takes a practical approach to print reading, with fundamental through advanced coverage that demonstrates industry standards essential for pursuing careers in the 21st century. Readers will learn step-by-step how to interpret actual industry prints while building the knowledge and skills that will allow them to read complete sets of working drawings. Realistic examples, illustrations, related tests, and print reading problems are based on real world engineering prints that comply with ANSI, ASME, AWS, and other related standards